Young football players have significantly more spinal changes on MRI compared to non-athletes - Witwit, W.; Thoreson, O.; Swärd Aminoff, A.; Todd, C.; Jonasson, P.; Laxdal, G.; Hebelka, H.; Baranto, A. (Translational Sports Medicine, 2020)
Purpose: Evidence-based facts regarding spinal abnormalities and back pain in young athletes are needed in order to be able to adapt rehabilitation programs and preventive measures accordingly. The aim of this study was therefore to identify MRI changes in the thoracolumbar spine and the lifetime prevalence of back pain in young football players compared to non-athletes. Methods: Young elite football players (n = 27) and non-athletes (n = 26) completed MRI examinations of the thoracolumbar spine. MRI images were evaluated for disk signal, height, bulging, herniation, Schmorl's nodes, spondylolisthesis, and vertebral wedging. All participants answered questionnaires regarding training hours and back pain. Results: Disk degenerative changes were more commonly displayed by 89% of the football players compared to 54% of the controls (P = .006). Schmorl's nodes (22%), disk herniation (30%), and reduced disk height (37%) were more prevalent in football players compared to controls (0%) (P = .023 and P = .001, respectively). The lifetime prevalence of back pain was reported by 52% of football players and 44% of controls, a difference that was not statistically significant. Conclusion: Young male football (soccer) players have more degenerative disk changes compared to non-athletes. Both groups displayed high lifetime prevalence of back pain.